Pragmatic diplomacy and new partners in Africa: a case study of South Korea-Africa relations - Matji, Thato Minah (My University, 2020)
South Korea‘s economic story is remarkable; it has transitioned from a resource poor, low-income nation to a high-income economy in only three decades. As a new development partner on the African continent it has been given little attention. Its role on the continent is important in complimenting Africa‘s path to development; however South Korea still needs to articulate its African strategy clearly in order to achieve a mutually beneficial partnership that it promotes on different platforms. This research seeks to uncover the nature of the South Korea-Africa relations and how South Korea has made efforts through the different platforms such as the Korea-Africa Forum and Korea-Africa Economic Cooperation to contribute to Africa‘s development path. This research paper also seeks to interrogate whether South Korea as a new player on the continent is bringing in a unique strategy or if it is following in the path of the old players and most importantly revealing whether the diplomatic interactions between African countries and South Korea are yielding practical results. A qualitative research method will be used for this study to reveal important phenomena which will give a broader and critical understanding of international relations, particularly international cooperation. South Korea considers its relation with developing countries as a partnership and that of friendship and this is changing the dynamics of development partners. This research provides an in-depth analysis of what it means to forge partnerships based on mutual understanding. African countries are faced with a myriad of development challenges and the history of development strategies have revealed that a one-size fits all approach is not effective in achieving sustainable development. This research report interrogates how South Korea is adopting to the African experiences of development challenges through its diplomatic interactions and through a number of projects. Technological advancement is moving at a fast pace and African governments such as in Rwanda have identified the importance of a knowledge-based economy. As a technological giant, South Korea has taken up the role of transferring its knowledge and skills to African countries. South Korea‘s experience in rural development through the New Village Movement offers African countries to adopt similar strategies to bridge the gap between rural and urban areas
A research report submitted in partial fulfilment of the requirements for the Degree of Master of Arts in International Relations, Department of International Relations, Faculty of Humanities, 2020